Physical and Chemical Mutation for Enhanced Alpha-Amylase Production by Aspergillus fumigatus NTCC1222 under Solid State Fermentation Conditions Using Agri-Residue Waste - Shalini Singh,; Sanamdeep Singh ,; Jyoti Mangla, (Journal of Pharmacy and Nutrition Sciences, 2016)
The search for better microbial sources of enzymes has long been an area of active research owing to the clear and distinct importance in todays’ world where exploration and application of environment friendly products has become a necessity. Though the natural, wild microbial strains, are continuously be searched and explored for their potential for amylase production yet, simultaneous attempts for improved enzyme production are necessary too. In the present study, a comparison between the influence of different mutational treatments (UV treatment and EMS-EtBr treatment) on amylase production was studied. Aspergillus fumigatus NTCC1222, an indigenously isolated amylase producer, which has shown an amylase activity of 341.7 U/mL under optimized conditions of SSF in our previous study, was subjected to UV- and EMS-EtBr- treatment for possible improved amylase production under optimized solid state fermentation conditions. The UV mutated strains yielded an amylase production of 614.2 U/mL while the chemically (EMS-EtBr) mutated strain produced 814.1 U/mL of amylase activity thereby indicating the successful enhancement in amylase activity for the test fungal strain.